Developing the kovacs on high bar - Irwin, G.; Kerwin, D.; Manning, M.; Brown, R. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study was to evaluate the tucked Kovacs as a preparatory activity for the development of the more complex straight and full twisting Kovacs. Twin video images of Kovacs (tucked n=7; straight n=3; and full twisting n=5) were collected at the 2000 Sydney Olympics. 3D_DLT analyses were used to determine joint angular kinematics and combined with customised body segment inertia parameters to determine normalised angular momenta. Angular kinematic similarities were found between the three Kovacs variants but there were large differences in normalised angular momentum between the tucked and straight Kovacs. Identifying appropriate preparatory activities is desirable to make training more effective, and in particular when trying to increase angular momentum in order to develop the straight from the tucked Kovacs.